The Ambiguous Neighbour: Female Neighbourhood Networks and the Parable of the Lost Coin - Kartzow, Marianne Bjelland (Neotestamentica, 2019)
In this article, I will draw on intersectional feminist theory and interdisciplinary neighbour studies. My point of departure is the rich and complex reception of the Hebrew Bible phrase, "love your neighbour as yourself" (Lev 19:18). What is love and who is a neighbour? And what about the stranger? I will suggest an alternative reading of the so-called parable of the lost coin in the Gospel of Luke (15:8-10) and propose a re-naming of the story to the parable of the found neighbours. By highlighting not only the woman or the lost coin, but the female neighbours she invites to celebrate when she finds it, a broader social and cultural context for the parable will be presented. My aim is to use this apparently "un-colourful" one-verse story as a starting point for "asking the other question" and for creative re-imagination of female neighbours among Christ-following groups.